Characteristic Features in the Novels of Contemporary Indian English Novelist Anita Desai and Kamala Markandeya: A Comparative Study: Exploring the Dynamics of Relationships in the Novels of Anita Desai and Kamala Markandeya (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Indian women writers in ongoing decades have delivered bounteous artistic yield. These writers test into human relationship since it is firmly associated with the brain and heart. So as to roll out the procedure of improvement smooth and extremely important, women writers have taken upon them-selves this awesome undertaking of their campaign against set up customs. It is simply after the Second World War that women novelists of value have started enhancing Indian fiction in English. Of these writers, Kamala Markandaya and Anita Desai are verifiably the most extraordinary. Many women writers have attempted their hands in the field of fictionnovels. Prior, novels centered the social and political issues of the society. There were stereotyped preparations or depiction of women characters and their parts. It is additionally evident that they were generally created by male novelists. Accordingly, they were the unbalanced introduction since they mirrored the perspectives, estimation of women from the comprehension of men. They were the impressions of the male feelings and encounters. After sometime the situation has changed. The novelists want to uncover the society and express the brain science of people. A Comparative Study of Selected Novels of Anita Desai and Kamala Markandaya tries to inspect the man-woman relationship as portrayed in the chose novels and furthermore investigates the manners in which the heroes have embraced to conquer the issues of their lives. A comparative investigation of the two novelists gives an intriguing and compensating background. Anita Desai and Kamala Markandaya are the two extraordinary specialists in the domain of English fiction. Be that as it may, aside from an article or two, relatively few studies have endeavored a comparative investigation of married Indian women in the novels of these two writers.